A stable PdCu@Pd core-shell nanobranches with enhanced activity and methanol-tolerant for oxygen reduction reaction. (10th September 2020) - Huang, Shaoda; Lu, Shuanglong; Hu, Hongyin; Cao, Binbin; Li, Huining; Duan, Fang; Zhu, Han; Gu, Hongwei; Du, Mingliang
Abstract: Palladium-based catalyst represents one of the most promising candidates among all non-platinum oxygen reduction reaction (ORR) catalysts. However, it is still challenging to precisely engineering their morphology and composition. Herein, highly branched core-shell PdCu@Pd nanocrystals have been fabricated via a simple one-pot synthesis that co-directed by hydrogen gas and halide ions. Such unique PdCu@Pd nanocrystals exhibit prominent ORR activity, durability and methanol-tolerance in alkaline media owing to their core-shell composition, highly-branched structure and defect-rich surface. This work elucidates a facile strategy to design highly branched core-shell nanomaterials, shedding light on the exploration and optimization of novel non-platinum ORR catalysts. Graphical abstract: A facile method for one-pot synthesis of Defect-rich PdCu@Pd Core-shell Nanobranches is developed. The as-made catalyst shows superior activity, durability and methanol-tolerance towards oxygen reduction reaction. Image 1